2014
DOI: 10.1128/jvi.02690-13
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin Receptor Specificity and Structural Analyses of Respiratory Droplet-Transmissible H5N1 Viruses

Abstract: h Two ferret-adapted H5N1 viruses capable of respiratory droplet transmission have been reported with mutations in the hemagglutinin receptor-binding site and stalk domains. Glycan microarray analysis reveals that both viruses exhibit a strong shift toward binding to "human-type" ␣2-6 sialosides but with notable differences in fine specificity. Crystal structure analysis further shows that the stalk mutation causes no obvious perturbation of the receptor-binding pocket, consistent with its impact on hemaggluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 22 publications
5
72
0
1
Order By: Relevance
“…To further characterize the receptor-binding specificity of the HA mutants with increased stability, we performed a glycan array analysis as described previously (13). Inactivated virus stocks were added to glass slide microarrays containing replicates of 58 diverse sialic acid-containing glycans found on avian (␣2,3-linked) and mammalian (␣2,6-linked) glycoproteins and glycolipids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further characterize the receptor-binding specificity of the HA mutants with increased stability, we performed a glycan array analysis as described previously (13). Inactivated virus stocks were added to glass slide microarrays containing replicates of 58 diverse sialic acid-containing glycans found on avian (␣2,3-linked) and mammalian (␣2,6-linked) glycoproteins and glycolipids.…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings by us (8,13) and others (9,12) demonstrated that HA heat stability and pH-dependent fusion activity contribute to the respiratory droplet transmissibility of avian H5 influenza viruses in mammals. In particular, mutations in H5 HA that conferred binding to human-type receptors reduced stability and increased the pH threshold for membrane fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that compensatory, HA-stabilizing mutations may therefore be critical for the selection of avian influenza viruses with human-type receptor specificity that are transmitted among mammals (58,59). Increased HA stability may also affect the pH at which HA undergoes an irreversible conformational change that is critical for HA-mediated fusion of the viral and endosomal membranes.…”
Section: Figmentioning
confidence: 99%
“…In addition, since the G219S substitution increased overall binding to avian and human receptors at the expense of HA stability, putative stability substitutions that would compensate for the decrease in HA stability caused by the G219S substitution were tested. Two substitutions-H103Y and T315I (H5 numbering)-were previously shown to increase the stability of A/H5N1 viruses via different mechanisms (10,11,(18)(19)(20). Using computational modeling (21), a N94K substitution located at the trimer interface of AN1 HA which could potentially have an impact similar to that seen with the H103Y substitution in HA of A/H5N1 was identified.…”
Section: R Ecent Human Infections With Influenza A/h7n9 Viruses Inmentioning
confidence: 99%